1995
DOI: 10.1016/0550-3213(94)00441-g
|View full text |Cite
|
Sign up to set email alerts
|

Quantum cosmology with Yang-Mills fields

Abstract: We examine an extension of the ideas of quantum cosmology and, in particular, the proposal of Hartle and Hawking for the boundary conditions of the Universe, to models which incorporate Yang-Mills fields. Inhomogeneous perturbations about a homogeneous, isotropic minisuperspace background model are considered, by expanding the Yang-Mills fields in harmonics of the spatial directions which are taken to be three-spheres. The expansions are made explicit for SO(N) gauge fields thereby obtaining formulae compatibl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…[12] the correspondence between Lifshitz-harmonics [14] and the harmonics derived from the representation matrices of G [13] has been established up to spin J = 2. For the scalar harmonics and the purely transverse vector and tensor harmonics it has been found that…”
Section: Appendicesmentioning
confidence: 99%
See 4 more Smart Citations
“…[12] the correspondence between Lifshitz-harmonics [14] and the harmonics derived from the representation matrices of G [13] has been established up to spin J = 2. For the scalar harmonics and the purely transverse vector and tensor harmonics it has been found that…”
Section: Appendicesmentioning
confidence: 99%
“…According to ref. [12] this arises automatically if the field χ is assumed to be close to one of its "classical" values χ = ±1. This assumption is well justified for a small gauge coupling e in which case the wave function for χ is strongly peaked around these values [16] (see eq.…”
Section: Harmonic Expansion Of So(3) Ym-theorymentioning
confidence: 99%
See 3 more Smart Citations